Active structural derivator in the design crystallization phase of L7e vehicle structures - Jedrzejczyk, Roman Pawel (Strojniški vestnik, 2019)
Over the past years, engineers have begun to apply topology optimization (TO) to obtain the first design proposals for new structures. Consequently, designers need to transform the bionic shapes of the TO results into manufacturable geometry that employs the available body-in-white structure types (BSTs) and affirms the efficient and suitable lightweight design. The lack of standardized methodologies, however, forces designers to transform the bionic shapes of the TO subjectively, which results in insufficient and inadequate design proposals. Many different separate geometrical transitions that attempt to transform the TO results into the one of the selected BSTs make the design process even more difficult to manage. For this reason, we have proposed the active structural derivator (ASD) as an extension of our existing integrative CAE-driven design process (ICDDP). The ASD allows for the smooth transition of the TO results and the practical assessment of the selected BSTs such as tubular space frame, space frame, hybrid structure, unibody and monocoque. Our ASD simultaneously employs the size and free-size optimizations under the specific steering criteria within one simulation model, which consists of fundamental engineering-based geometry (beams and plates), to generate the design concepts of the different BSTs for given sets of different requirements. We present the results of our ASD for the new structure of an electrified eQuad vehicle that reveal the ASD's ability to select, allocate and optimize various beam types (arbitrary and defined) together with the plate (shell) geometry. The results assert that the ASD enables engineers to deliver new applicable and lightweight structures.
Keywords: bionic geometry; bionska geometrija; body-in-white; design process; FEM; finite element method; free-size optimization; ICDDP; konstrukcijski proces; metoda končnih elementov; optimizacija velikosti; prosta optimizacija velikosti; size optimization; surova karoserija; topology optimization; topološka optimizacija; vehicle structure design; zasnova konstrukcije vozila